The Role of Islamic Family in Preventing Married By Accident Due to Promiscuity - Al Hakim, Muhamad Arief; Juniza, Lepia (Qanun: Jurnal Hukum Keluarga Islam, 2025)
The phenomenon of MBA arises due to pregnancy outside of marriage, which is often caused by free association. So that it causes couples who marry for this reason to be emotionally and financially unprepared. With the increase in free association, it is important for families to apply Islamic values as a preventive measure. Families play an important role in shaping children's character and preventing MBA. This study aims to analyze Islamic law in the application of Islamic values to children by families in order to avoid MBA due to free association. This study uses a descriptive qualitative method with a phenomenological approach, data was collected through observation in Apur Village, interviews with ideal families, MBA families, and the head of Apur Village, as well as documentation from several sources. The results of this study indicate that Married By Accident due to free association can be prevented by applying Islamic family values such as joining the Islamic youth community of the mosque, creating a harmonious atmosphere with children, and parental supervision of children, especially in the use of social media and sending children to Islamic boarding schools. So that with these values, families can avoid children from MBA.